ANALISIS ALIH FUNGSI LAHAN PERTANIAN DI KABUPATEN KEDIRI - Hidayat, Syarif Imam; Rofiqoh, Lisanul Latifatul (Jurnal Social Economic of Agriculture, 2020)
Kediri Regency as one of the Food Reserves in East Java experienced a decrease in the area of agricultural land due to land conversion in the period 2005-2016. Transfer of agricultural land functions is a serious threat to the sustainability and self-sufficiency of food, especially for the main food commodities namely rice, corn and soybeans. Transfer of function of agricultural land can cause the availability of agricultural land for sustainable food decreases. This study aims to: analyze the potential factors that affect the conversion of agricultural land, and analyze the extent of the influence of land conversion on the main food commodities(rice, corn, soybeans). The study uses secondary data from several related agencies, while determining the location is determined purposively. The data collected is then processeda analyzed using multiple linear regression. The results showed that the factors that had a significant influence on the conversion of agricultural land were population, industryand GRDP, while productivity (rice, corn, soybeans) and FTT had no significant effect.Keywords: Change of function of agricultural land, main food production